Fast Fourier Transform (FFT) Dalam Analisis Frekuensi Alat Musik Harmonika - Ida Bagus Made Surya Widnyana; Ngurah Agus Sanjaya ER (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
Music is an art of entertainment that has been installed in the world community. Many types of music and musical instruments are used to play a song / instrument. One of the musical instruments commonly used to accompany a musical strain. Harmonica is a wind instrument. How to play this instrument is by blowing and looking for holes to produce sound. Harmonica uses a sound source in the form of a vibrating plate (reed) which is attached to a vibrating plate (reedplate). When air is passed, the reed will respond by vibrating back and forth through the holes (slots) that have been made on the reed plate and produce sound. Fast Fourier Transform (FFT) is a transformation method/model that is usually used to represent voice signals in discrete time domains into voice signals in frequency domains/move time domain signals into frequency domains.